Analisis psikologi perkembangan menuju fase remaja - Arum, Putri Nirmala (Maliki Interdisciplinary Journal, 2024)
Judging from the many developmental theories, the adolescent phase is often labeled as a phase that often commits deviations and irregularities. Where the time during adolescence is the most active time to explore the world to find their identity. It is not uncommon for them to be hit by problems that confuse them because life as a teenager is also a phase of physical maturity which is accompanied by a phase of emotional maturity which is followed by the development of intelligence. The impact obtained is due to the pressures they face through the changes they experience or the impact of environmental changes. It turns out that personality in the adolescent phase is difficult to classify within the personality models seen at special ages. The many impacts of individual factors that participate in determining the shape of each teenager's personality, trigger observers of the complexity in arranging age lists along with personality shapes at certain ages. It is much easier to determine developmental sequences by patterns of behavior and the order in which those patterns emerge. As the transition occurs within each teenager, they will be faced with a variety of different burdens when they are still small.